Entry order, market share, and competitive advantage: A study of their relationships in new corporate ventures - Miller, Alex; Gartner, William B.; Wilson, Robert (Journal of Business Venturing, 1989)
This research explored the extent to which entry order (the decision to enter a market early as a “pioneer,” or to wait and follow) determines not only market share, but other competitive factors such as position and promotion that late entrants might hope to employ to overcome a pioneer's advantages. The study analyzed data on 119 nonservice new corporate ventures (consumer and industrial) from the Profit Impact of Marketing Strategy (PIMS) research data base, STR4. Based on a review of the strategic management and marketing literatures, three hypotheses on the effects of entry order were generated and subsequently tested. The first hypothesis states that pioneers achieve higher market shares than followers. Since, a priori, the market share for the pioneer has to be larger than the market share split among later entrants, the issue is the rate at which the early entrant's market share will decrease as additional businesses enter, what we term the “degree of lateness effect.” Later entrants have the choice of being an early follower, that is entering the industry soon after the pioneers, or waiting until the industry matures (late entrants). A high degree of lateness effect would indicate that early followers would gain higher market shares than late entrants. An analysis of the data indicated that pioneers have significantly higher market shares than followers and that little degree of lateness effect existed between early and late entrants. The second hypothesis states that pioneers will achieve differentiation advantages (in such areas as product and service quality, promotion, and technological positioning) greater than followers. There is considerable theoretical and empirical evidence that pioneers are able to generate competitive advantages through name recognition, image leadership, the establishment of technical standards which make switching to other products difficult, and superior consumer information advantages due to market lead times. An analysis of the data indicated that pioneers have significant competitive advantages in product/service quality and technology over followers. The one area where pioneers did not have a competitive advantage over followers was in advertising and promotion. The third hypothesis states that followers will achieve cost advantages greater than pioneers. While learning curve theory suggests that pioneers will enjoy cost/price advantages, contrasting arguments can be made that followers can enjoy lower costs by “coattailing” on the pioneer's efforts to educate consumers, develop a dominant design, and create an infrastructure to span the gap from raw material suppliers to finished good deliveries. We suggest that because pioneers are likely to have attained differentiation advantages, followers will have only one alternative left: compete on the basis of price and become the lowest-cost producer. An analysis of the data indicates that while followers do appear to have lower prices than pioneers, followers do not have significantly lower cost structures. This result implies a lower level of profitability for a follower strategy. Overall, the results of this study advance the notion that new corporate ventures should enter as pioneers, rather than as followers. Pioneers had higher market shares and stronger competitive positions (higher quality, more differentiated products, and better service) than followers. Followers appear to have few successful competitive options available outside of promotion for gaining market share.